PRESENCE OF IUS COMMUNE PROCEDURE FEATURES IN MODERN POLISH CIVIL PROCEEDINGS - Skibińska, Magdalena (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
Social dissatisfaction with the administration of justice in Poland is closely related to excessive delays in resolving civil disputes. However, this disadvantage is only an outcome of complex and outdated regulations. Therefore, the Polish legislator in recent years have introduced various new solutions that were supposed to modernize the civil procedure and accelerate the speed of proceedings. Some of them resemble the medieval ius commune procedure features. The main purpose of this paper is to identify them and discuss their reasonableness as well as their usefulness in modern civil proceedings from the historical perspective. The conducted research leads to the conclusion that the described reform efforts are contrary to the basic principles of civil procedure developed over the years such as orality, publicity or immediacy and cannot contribute to the expected positive effect in terms of ensuring the right to court without undue delay. On the contrary, only open and direct communication between a court and the parties, simplified procedural rules and increased number of court staff can guarantee the efficiency of the proceedings.